Technology transfer and its impact on innovation and firm performance: empirical evidence from Turkish export companies - Cinar, Omer; Altuntas, Serkan; Alan, Mehmet Asif (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The purpose of this study is to determine the relationships between technology transfer, innovation and firm performance. Design/methodology/approach The relationship between technology transfer, innovation and firm performance is examined by using data obtained from 252 Turkish export firms, which are among the top 1,000 firms in terms of export volume in Turkey. To examine these relationships, a theoretical framework is empirically tested using structural equation modeling and tested via an empirical study of Turkish export companies. Findings The results of this study can benefit policymakers in government at the national level and company decision-makers at the firm level. Furthermore, an understanding of the relationship between technology transfer, innovation and firm performance may help firms to make correct technology transfer decisions and focus on the correct type of innovation to increase firm performance in practice. The findings indicate the positive effects of technology transfer on innovation and firm performance. In addition, innovation mediates the relationship between technology transfer and firm performance in Turkish export companies. This study suggests that decision-makers should transfer the right technology because well-realized technology transfers lead to the improvement of corporate innovation capacities and improvement of firm performances for export companies. Originality/value There is no study that fully examined the relationship between technology transfer, innovation and firm performance. The proposed literature-based theoretical framework in this study is novel for Turkish export companies.
Keywords: Innovation; Technology transfer; Firm performance; Structural equation modeling; ORGANIZATIONAL INNOVATION; CORPORATE CULTURE; MANAGEMENT; CAPABILITY; KNOWLEDGE; INDUSTRY; Computer Science